Murottal Audio as a Medium for Memorizing the Qur’an in Super-Active Children - Susi Safitri; Mahmeed Alii; Omar Mahmud (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The study aimed to develop murottal audio media as a medium for memorizing the Qur’an in tahfiz learn this the schools of scholars boarding school payakumbuh. Learning tahfiz that uses murottal audio as a medium for memorizing the Qur’an will make the child even more excited in improving the improve onroveon. Every child who is given mutual audio will make a positive impact in continuing their memorization, the study therefore feelrefeel that beneficial helpful for student beneficialg out the recitation of the Qur’an seta in memorizing the Qur’totalottal audio applications straightforward effortless to get and also easy to download on mobile phones because increasingly sophisticated and modern technology makes it easy for us to get them. Making students easy to get as well as in any application even on social media, namely youtube, Instagram, WhatsApp, TikTok, vidmate and the Qur’an application. A media will have an impact if used appropriately. Therefore teachers must be wise in explaining the media to their students. Learning in which there is a medium will make the media significantly letediousiare. are there is media, dsssenly want to pay attention to the lessons given by their teachers, so in order not to happen boring lessons, a medium is needed in the learning process so that students are more enthusiasti about in a letherning that takes place.